Stabilization of organic clay usinglime-added salt - Mohd. Yunus, Nor Zuraihetty (2007)
The main objective of this research is to investigate effectiveness of salts used as an additive in lime-stabilized organic clay. Lime is known to be an effective stabilization method for clayey soil. However for organic clay it becomes less effective due to low increase in strength. Therefore salts are used to accelerate lime-organic clay reactions. Salts are introduced to remove the barrier in order to accelerate as well as help lime to increase the strength of soil. Two types of salts used are sodium chloride (NaCl) and calcium chloride (CaCl2). The unconfined compressive test (UCT) is conducted on 108 remolded samples (38mm x 80mm) for 0,7,14 and 28 days of curing period. The test results indicated that when NaCl or CaCl2 is added to the lime-organic clay mixture, the strength of mixture increases with increasing salt concentration. The strength of clay stabilized with lime and sodium chloride is higher than clay stabilized with lime and calcium chloride at a 10% salt concentration. The highest unconfined compressive strength (UCS) achieved is 777kPa for clay stabilized with 10% lime and 10% NaCl cured at 28 days.